Investigating The Relationship Between University Students’ Perceptions of Themselves as Writers and Their Writing Performance - Beleta, Dejene Mendera; Kebede, Seime (Pascasarjana Universitas Negeri Makassar, 2023)
This study was aimed at investigating the relationship between EFL students’ perceptions of themselves as writers and their writing performances in an EFL setting with particular reference to first-year undergraduate students at Dire Dawa University, Ethiopian. To the researcher’s best knowledge, how EFL students perceive themselves as writers when writing in English and its relationship and influence on their writing performance was an undiscovered area in the Ethiopian tertiary level contexts. The study used a mixed method research approach of correlational design. As a result, data for the study were collected using questionnaires, writing tests, and interviews, and were analyzed quantitatively and qualitatively. The findings of the study revealed that there is a positive relationship between students’ perceptions of themselves as writers and their writing performances though there is no statistically significant relationship between these two variables. The research results also revealed that students had average perceptions of themselves as writers and their writing performance was found low. Moreover, the results of the study show that students writing performance is influenced by their general progress and physiological state. Generally, it was understood that students’ perceptions of themselves as writers have a positive relationship, and influence on their writing performance levels.